Assessment of Impact of Patient Recruitment Volume on Risk Profile, Outcomes, and Treatment Effect in a Randomized Trial of Ticagrelor Versus Prasugrel in Acute Coronary Syndromes - Gjin Ndrepepa (Wiley, 2021)
BACKGROUND Whether there are differences in the risk profile and treatment effect in patients recruited in a low recruitment center (LRC) versus patients recruited in a high recruitment center (HRC) in a randomized multicenter trial remains unknown. METHODS AND RESULTS This study included 4018 patients with acute coronary syndrome recruited in the ISAR‐REACT 5 (Intracoronary Stenting and Antithrombotic Regimen: Rapid Early Action for Coronary Treatment 5) trial. The primary end point was a composite of all‐cause death, myocardial infarction, or stroke. Overall, 3011 patients (75%) were recruited in the HRCs (7 centers recruiting 258 to 628 patients; median, 413 patients) and 1007 patients (25%) were recruited in the LRCs (16 centers recruiting 5 to 201 patients; median, 52 patients). Patients recruited in the LRCs had more favorable cardiovascular risk profiles than patients recruited in the HRCs. The primary end point occurred in 72 patients in the LRCs and 249 patients in the HRCs (cumulative incidence, 7.3% and 8.4%; P=0.267). All‐cause mortality was lower among patients recruited in the LRCs (n=29) than among patients recruited in the HRCs (n=134; cumulative incidence 2.9% versus 4.5%; P=0.031). There was no significant interaction between the treatment effect of ticagrelor versus prasugrel and patient recruitment category (LRC versus HRC) regarding the primary efficacy end point (LRC: hazard ratio [HR], 1.42 [95% CI, 0.89–2.28]; HRC: HR, 1.33 [95% CI, 1.04−1.72]; P for interaction=0.800). CONCLUSIONS Patients with acute coronary syndrome recruited in a LRC appear to have more favorable cardiovascular risk profiles and lower 1‐year mortality rates compared with patients recruited in a HRC. The recruitment volume did not interact with the treatment effect of ticagrelor versus prasugrel. REGISTRATION URL: https://www.clinicaltrials.gov; Unique identifier: NCT01944800.